Pinay on the prairies : Filipino women and transnational identities - Bonifacio, Glenda Tibe, 1963- (UBC Press, 2013)
For many Filipinos, one word kumusta, how are you is all it takes to forge a connection with a stranger anywhere in the world. In Canada's Prairie provinces, this connection has inspired community building and created both national and transnational identities for the women who identify as Pinay. This book is the first to look beyond traditional metropolitan hubs of settlement to explore the migration of Filipino women in Alberta, Manitoba, and Saskatchewan. Based on interviews with first-generation immigrant Filipino women and temporary foreign workers, this book explores how the shared experience of migration forms the basis for new identities, communities, transnational ties, and multiple levels of belonging in Canada. A groundbreaking look at the experience of Filipino women in Canada, Bonifacio's work is simultaneously an investigation of feminism, migration, diaspora, and the rubric of multiculturalism in a global era.